INFLUENCE OF SULFITATION ON THE DYNAMICS OF THE ACTIVITY OF OXIDIZING ENZYMES IN WHITE GRAPES - Traian Hopulele; Gabriela Rapeanu; Aurel Ciubucă; Elena Postolache; Carmen Popescu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Sulfur dioxide is used to control the browning of the wine, but it is known as an irritating agent of the digestive mucous membrane, of the lungs, and, at the same time, it destroys the thiamine, therefore the admissible quantities in vinification have been reduced. The research focused on the influence of different SO2 doses on the oxidizing enzymes found in grapes, in the must, and in the young wine. During the alcoholic fermentation the activity of the oxidizing enzymes dropped by 74.3 - 87.50and the laccase was deactivated when doses of 50 - 75 mg.L-1 SO2 were used. The activity of the polyphenoloxidase (tyrosinase and laccase) gradually decreased during the alcoholic fermentation. Using the same doses of SO2, after the alcoholic fermentation, there has been noted a reduction of 56.6 - 71.80of the activity of the peroxydase in wine compared to the first day of the alcoholic fermentation.